A new look at the tourism development and economic growth nexus: International evidence. Issue 8 (December 2021) - Benkraiem, Ramzi; Lahiani, Amine; Miloudi, Anthony; Shahbaz, Muhammad
This article tests the relationship between tourism development and economic growth in major tourism destinations in the world. The study relies on the quantile autoregressive distributed lag model. The main findings show a nonlinear cointegrating relationship between tourism development and economic growth in France, Mexico, Spain, and Italy. Indeed, in these countries, the long-run cointegrating parameter and speed of adjustment parameter differ across quantiles of economic growth distribution. They also show a nonlinear contemporaneous and lagged influence of tourism development on economic growth except in China and Germany. These differences between countries may be attributed to differences in the relative weight of the tourism industry in the overall economy of each country, whereas the differences across quantiles may be explained by the negative externalities caused by tourism growth. These findings have important policy and decision implications because tourism has differing impacts on economic growth in the short and long run in major tourism destinations. Thus, they may have new and helpful insights in planning for tourism development policies that facilitate the stimulation of economic growth.